A high-efficiency thermal transfer carbon ribbon back coating adhesive and preparation method thereof
By synthesizing the crosslinked silicone acrylic copolymer and using a single component toluene solvent, the problems of high curing temperature, poor adhesion, poor anti-static and flame retardant properties of the thermal transfer carbon belt back coating are solved, and efficient and environmentally friendly thermal transfer carbon belt back coating preparation is achieved, which significantly improves its anti-static, flame retardant and heat resistance.
Patent Information
- Application Number
- CN202411377282.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The existing thermal transfer carbon tape back coating has problems such as high curing temperature, poor adhesion, poor anti-static and flame retardant properties, and the use of multi-component solvents leads to contamination and high costs.
By synthesizing the crosslinked silicone acrylic copolymer, diluted with a single component toluene solvent, a cage-shaped silicone monomer containing quaternary phosphonium salt and fluorine elements is formed, and polymerization is initiated to improve the antistatic, flame retardant and heat resistance of the back-coated glue.
It significantly improves the anti-static, flame retardant and high-temperature resistance of back-coated glue, reduces the amount of solvent used, reduces production costs, and improves the heat conduction and lubrication effect during printing.
Smart Images

Figure BDA0005068999770000051 
Figure BDA0005068999770000052 
Figure BDA0005068999770000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal transfer carbon ribbons, in particular to a high-efficiency thermal transfer carbon ribbon back coating adhesive and a preparation method thereof. Background Art
[0002] Thermal transfer technology is one of the digital printing technologies currently in use. Its principle is to transfer heat-sensitive ink to the image-receiving medium through heat. The back-coating adhesive of thermal transfer carbon ribbon is a special coating material, which is located on the side where the transparent film (such as PET substrate) contacts the print head. It is designed to prevent direct contact between the carbon ribbon and the print head and reduce wear of the print head. The earliest back-coating adhesive used in China was the silicone resin / curing agent system. Its disadvantages are that it is a two-component system with a short shelf life, high curing temperature, and poor adhesion to the PET substrate, so it can only be used for low-end products. Later, acrylic resin-modified silicone was used. The adhesion of this material to the substrate was enhanced, but the brittleness of the coating became greater, the printer made a lot of noise during use, and the coating easily adhered to the print head, thereby reducing the printing quality. With the development of thermal transfer materials and the continuous advancement of thermal transfer technology, the existing back-coating adhesive materials can no longer meet the demand for thermal transfer materials.
[0003] Thermal transfer ribbons generally use polyethylene terephthalate (PET) as the base film, and a back-coating adhesive is applied on it to meet various application requirements; the thermal transfer ribbons of the prior art have the following defects: the multi-component back coating with silicone adhesive as the main body has a high curing temperature after film formation; although the introduction of acrylic acid segments reduces the curing temperature, the acrylic acid segments have low heat resistance, which ultimately narrows the application window of the ribbon on high-end resin bases, reduces the sliding property, and easily contaminates the print head during long-term printing. In addition, static electricity is easily generated during the conventional ribbon winding and slitting processes, and the release of static electricity can easily cause damage to the print head; in the precision coating industry, anti-static devices are generally used in combination with static brushes, static ropes, static rods, etc., but they can only eliminate the static electricity generated during winding and unwinding during the coating process, and cannot eliminate the static electricity generated during the actual application process. At the same time, the poor flame retardant performance makes it easy to cause fires.
[0004] Chinese patent CN114656601B discloses a method for preparing an acrylate-modified silicone polymer and its application in thermal transfer ribbons. The method uses a double-terminal allyl silicone monomer and trimethylolpropane triacrylate as main monomers. Under the condition of an initiator, a cross-linked acrylic modified silicone polymer with a hyperbranched structure is synthesized through a free radical polymerization addition reaction of double-building and double-building. The polymer is applied to the back coating of a resin-based thermal transfer ribbon. The prepared back coating has good adaptability in all aspects, but does not significantly improve the thermal transfer ribbon's resistance to corrosion. The invention discloses a novel cross-linked organic silicon acrylic copolymer, which has good antistatic and flame retardant properties, and uses multi-component solvents such as butanone, toluene and cyclohexanone as diluents, which has high pollution and high cost. The invention aims to synthesize a double-terminal alkenyl caged organic silicon monomer containing quaternary phosphonium salt and fluorine element, and initiates polymerization with four double bonds of pentaerythritol tetraacrylate. After the cross-linked organic silicon acrylic copolymer is diluted with a single-component toluene solvent, the antistatic, flame retardant and heat-resistant properties of the thermal transfer carbon ribbon are significantly improved. The safe recycling of the single-component solvent toluene reduces the solvent usage by 99%, thereby reducing the production cost. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a high-efficiency thermal transfer carbon ribbon back coating adhesive and a preparation method thereof. By introducing a cross-linked structure, the back coating adhesive has a stronger adhesion to the substrate, thereby alleviating the problems of high curing temperature and poor adhesion to the substrate of the existing silicone resin system, and significantly improving the antistatic, flame retardant and high temperature resistance of the back coating adhesive.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] A method for preparing a high-efficiency thermal transfer carbon ribbon back coating adhesive is carried out according to the following steps:
[0008] Step (1), under nitrogen atmosphere, add pentaerythritol tetraacrylate and deionized water to a reaction flask, disperse them uniformly, and then add The diene fluorine-containing caged siloxane monomer and the initiator are polymerized at 75-90° C. for 1-3 hours, the temperature is lowered to 45-55° C., and the pH is adjusted to 8-9 with aqueous ammonia to obtain a cross-linked silicone acrylic copolymer.
[0009] Step (2), dissolving 8-12% by weight of the cross-linked silicone acrylic copolymer in 88-92% toluene, and after it is evenly diluted, directly coating it on the back of the resin-based thermal transfer ribbon on a coating machine using a gravure coating method, with a coating amount of 0.05-0.25 g / m 2 , and obtain a highly efficient thermal transfer carbon ribbon back coating.
[0010] Preferably, the initiator in step (1) is any one of potassium persulfate, ammonium persulfate or benzoyl peroxide.
[0011] Preferably, in step (1), the molar ratio of pentaerythritol tetraacrylate, diene fluorine-containing caged siloxane monomer, and initiator is 1:0.5-0.8:0.02-0.05.
[0012] Preferably, the preparation method of the diene fluorine-containing caged siloxane monomer in step (1) is carried out according to the following steps:
[0013] Step S1, under a nitrogen atmosphere, add tetrakis(hydroxymethyl)phosphonium chloride and a solvent to a reaction flask equipped with a tail gas absorption device, stir evenly, add vinyltrichlorosilane, stir to react, after the reaction is completed, cool and crystallize, filter, wash the filter cake with acetonitrile, and dry to obtain an alkenyl cage siloxane monomer.
[0014] Step S2, under a nitrogen atmosphere, add 2,5-bis(trifluoromethyl)terephthalic acid, alkenyl cage siloxane monomer and dichloromethane into a reaction flask, stir evenly, add 4-dimethylaminopyridine and N,N-dicyclohexylcarbocyanine, stir to react, after the reaction is completed, distill under reduced pressure, and recrystallize from ethanol to obtain a diene fluorine-containing cage siloxane monomer.
[0015] Preferably, the solvent in step S1 is any one of diethylene glycol dimethyl ether, N,N-dimethylformamide, and xylene.
[0016] Preferably, in step S1, the molar ratio of tetrakis(hydroxymethyl)phosphonium chloride to vinyltrichlorosilane is 1:1.5-1.8.
[0017] Preferably, in step S1, the reaction temperature is 120-140° C., and the reaction time is 5-12 h.
[0018] Preferably, in step S2, the molar ratio of 2,5-bis(trifluoromethyl)terephthalic acid, alkenyl cage siloxane monomer, 4-dimethylaminopyridine and N,N-dicyclohexylcarbodiimide is 1:2.05-2.2:0.3-0.5:2.5-3.2.
[0019] Preferably, in step S2, the reaction temperature is 20-35° C. and the reaction time is 12-24 h.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) Long-lasting antistatic performance: The cross-linked silicone acrylic copolymer contains quaternary phosphonium salt. The phosphorus atom ion radius in the quaternary phosphonium salt is large, which enhances its polarization effect and makes it easier to interact with negatively charged charges or substances through electrostatic action, forming a stable protective layer on the surface of the substrate, thereby quickly conducting the static charge generated during the printing friction process away from the material surface, so that the generated static charge does not accumulate; at the same time, the quaternary phosphonium salt is chemically grafted with acrylic monomers to initiate polymerization and is bonded to the main body of the material in the form of a cross-linked network structure. Therefore, the antistatic performance will not migrate and lose over time, and it has a long-lasting antistatic effect.
[0022] (2) Excellent flame retardant properties: The phosphorus and silicon in the cross-linked silicone acrylic copolymer can produce synergistic flame retardancy. Phosphorus will catalyze the formation of carbon, while caged silicon will increase the thermal stability of these carbon layers. The acidic gas released by phosphorus combines with silicon to form silicates, which promotes the formation of phosphate compounds. The layered silica formed by the degradation of siloxane can prevent the oxidation of the carbon layer, forming a more complete protective film that can more effectively isolate heat and oxygen and delay the combustion process. On the other hand, the cross-linked silicone acrylic copolymer is obtained by initiating polymerization of the two double bonds of the double-terminal alkenyl caged silicone monomer and the four double bonds of pentaerythritol tetraacrylate, which can form a hyperbranched cross-linked network structure. When the material burns, it can form a dense protective layer that can isolate oxygen from the internal material, thereby slowing down or preventing the combustion process.
[0023] (3) Good printing and back coating effects: The fluorine element in the back coating glue forms a fluorocarbon protective film on the surface of the carbon ribbon, which can not only reduce the friction coefficient and improve the wear resistance of the surface, but also prevent the occurrence of problems such as corrosion and adhesion; the fluorine element has extremely high chemical stability, its atomic radius is small, and its electronegativity is strong, so that the chemical bonds in the fluoride molecules are very strong, and they will not fail due to thermal decomposition or chemical reaction in a high temperature environment, thereby maintaining their lubrication properties. The carbon ribbon back coating glue prepared by the present invention has good heat resistance and wear resistance, and prints smoothly and has good bonding performance. It strengthens the heat conduction and lubrication effect during the printing process, and can effectively alleviate the problem of print head wear.
[0024] (4) Environmentally friendly and recyclable: Under the same function as the carbon tape back coating, the product of the present invention has a much lower usage per unit area than the existing product. The single-component solvent toluene is used to replace the multi-component mixed solvent, so that the solvent can be safely recycled, reducing the solvent usage and VOC emissions during the product production process, protecting the environment and reducing production costs. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Unless otherwise specified, the raw materials and reagents used in this application are commercially available or can be prepared by known methods.
[0027] Tetrakis(hydroxymethyl)phosphonium chloride, CAS number is 124-64-1.
[0028] Vinyltrichlorosilane, CAS number is 75-94-5.
[0029] 2,5-Bis(trifluoromethyl)terephthalic acid, CAS number is 366008-67-5.
[0030] Pentaerythritol tetraacrylate, CAS No. 4986-89-4, structural formula:
[0031]
[0032] Example 1
[0033] (1) Under nitrogen atmosphere, 56 mmol of tetrakis (hydroxymethyl) phosphorus chloride and 450 mL of diethylene glycol dimethyl ether were added to a reaction flask equipped with a tail gas absorption device, and after stirring evenly, 92.4 mmol of vinyl trichlorosilane was added, and the mixture was reacted at 130° C. for 10 h, cooled and crystallized, filtered, and the filter cake was washed with acetonitrile and dried to obtain an alkenyl cage siloxane monomer. The preparation reaction formula is as follows:
[0034]
[0035] (2) Under nitrogen atmosphere, add 50 mmol of 2,5-bis(trifluoromethyl)terephthalic acid, 107 mmol of alkenyl cage siloxane monomer and 625 mL of dichloromethane to the reaction flask, stir evenly, add 20 mmol of 4-dimethylaminopyridine and 140 mmol of N,N-dicyclohexylcarbodiimide, react at 25°C for 16 h, distill under reduced pressure, and recrystallize from ethanol to obtain a diene fluorine-containing cage siloxane monomer. The preparation reaction formula is as follows:
[0036]
[0037] (3) Under a nitrogen atmosphere, 10 mmol of pentaerythritol tetraacrylate and deionized water were added to a reaction flask. After uniform dispersion, 5 mmol of diene fluorinated cage siloxane monomer and 0.35 mmol of potassium persulfate were added, and polymerization was carried out at 80° C. for 2 h. The temperature was lowered to 50° C., and the pH was adjusted to 9 with aqueous ammonia to obtain a cross-linked silicone acrylic copolymer.
[0038] (4) 8% by weight of cross-linked silicone acrylic copolymer was dissolved in 92% toluene. After being evenly diluted, it was directly coated on the back of the resin-based thermal transfer ribbon using a gravure coating machine. The coating amount was 0.05 g / m 2 , and obtain a highly efficient thermal transfer carbon ribbon back coating.
[0039] Example 2
[0040] (1) Under nitrogen atmosphere, 120 mmol of tetrakis(hydroxymethyl)phosphonium chloride and 600 mL of N,N-dimethylformamide were added to a reaction flask equipped with a tail gas absorption device, and after stirring, 180 mmol of vinyltrichlorosilane was added, and the mixture was reacted at 140° C. for 5 h, cooled and crystallized, filtered, and the filter cake was washed with acetonitrile and dried to obtain an alkenyl cage siloxane monomer.
[0041] (2) Under nitrogen atmosphere, 110 mmol of 2,5-bis(trifluoromethyl)terephthalic acid, 225.5 mmol of alkenyl cage siloxane monomer and 880 mL of dichloromethane were added to a reaction flask. After stirring evenly, 33 mmol of 4-dimethylaminopyridine and 275 mmol of N,N-dicyclohexylcarbodiimide were added. The mixture was reacted at 35° C. for 12 h, and then distilled under reduced pressure and recrystallized from ethanol to obtain a diene fluorine-containing cage siloxane monomer.
[0042] (3) Under a nitrogen atmosphere, 10 mmol of pentaerythritol tetraacrylate and deionized water were added to a reaction flask. After uniform dispersion, 6 mmol of diene fluorinated caged siloxane monomer and 0.2 mmol of ammonium persulfate were added, and polymerization was carried out at 90° C. for 1 h. The temperature was lowered to 55° C., and the pH was adjusted to 8 with aqueous ammonia to obtain a cross-linked silicone acrylic copolymer.
[0043] (4) A 9% cross-linked silicone acrylic copolymer was dissolved in 91% toluene. After being evenly diluted, it was directly coated on the back of the resin-based thermal transfer ribbon using a gravure coating machine. The coating amount was 0.1 g / m 2 , and obtain a highly efficient thermal transfer carbon ribbon back coating.
[0044] Example 3
[0045] (1) Under a nitrogen atmosphere, 35 mmol of tetrakis(hydroxymethyl)phosphonium chloride and 350 mL of xylene were added to a reaction flask equipped with a tail gas absorber. After stirring, 63 mmol of vinyltrichlorosilane was added, and the mixture was reacted at 120° C. for 12 h. The mixture was cooled and crystallized, filtered, and the filter cake was washed with acetonitrile and dried to obtain an alkenyl cage siloxane monomer.
[0046] (2) Under nitrogen atmosphere, 30 mmol of 2,5-bis(trifluoromethyl)terephthalic acid, 66 mmol of alkenyl cage siloxane monomer and 450 mL of dichloromethane were added to the reaction flask, and after stirring evenly, 15 mmol of 4-dimethylaminopyridine and 96 mmol of N,N-dicyclohexylcarbodiimide were added, and the mixture was reacted at 20° C. for 24 h, and then distilled under reduced pressure and recrystallized from ethanol to obtain a diene fluorine-containing cage siloxane monomer.
[0047] (3) Under a nitrogen atmosphere, 10 mmol of pentaerythritol tetraacrylate and deionized water were added to a reaction flask. After uniform dispersion, 7 mmol of diene fluorinated caged siloxane monomer and 0.5 mmol of benzoyl peroxide were added, and polymerization was carried out at 75° C. for 3 h. The temperature was lowered to 55° C., and the pH was adjusted to 9 with aqueous ammonia to obtain a cross-linked silicone acrylic copolymer.
[0048] (4) 10% by weight of cross-linked silicone acrylic copolymer was dissolved in 90% toluene. After being evenly diluted, it was directly coated on the back of the resin-based thermal transfer ribbon using a gravure coating machine. The coating amount was 0.15 g / m 2 , and obtain a highly efficient thermal transfer carbon ribbon back coating.
[0049] Example 4
[0050] (1) Under a nitrogen atmosphere, 70 mmol of tetrakis(hydroxymethyl)phosphonium chloride and 500 mL of diethylene glycol dimethyl ether were added to a reaction flask equipped with a tail gas absorber. After stirring evenly, 115 mmol of vinyltrichlorosilane was added, and the mixture was reacted at 135° C. for 8 h. The mixture was cooled and crystallized, filtered, and the filter cake was washed with acetonitrile and dried to obtain an alkenyl cage siloxane monomer.
[0051] (2) Under nitrogen atmosphere, 60 mmol of 2,5-bis(trifluoromethyl)terephthalic acid, 127.2 mmol of alkenyl cage siloxane monomer and 810 mL of dichloromethane were added to a reaction flask. After stirring evenly, 27 mmol of 4-dimethylaminopyridine and 170 mmol of N,N-dicyclohexylcarbodiimide were added. The mixture was reacted at 30° C. for 15 h, and then distilled under reduced pressure and recrystallized from ethanol to obtain a diene fluorine-containing cage siloxane monomer.
[0052] (3) Under a nitrogen atmosphere, 10 mmol of pentaerythritol tetraacrylate and deionized water were added to a reaction flask. After uniform dispersion, 7 mmol of diene fluorinated cage siloxane monomer and 0.25 mmol of potassium persulfate were added, and polymerization was carried out at 85° C. for 2 h. The temperature was lowered to 50° C., and the pH was adjusted to 9 with aqueous ammonia to obtain a cross-linked silicone acrylic copolymer.
[0053] (4) 11% by weight of cross-linked silicone acrylic copolymer was dissolved in 89% toluene. After being evenly diluted, it was directly coated on the back of the resin-based thermal transfer ribbon using a gravure coating machine. The coating amount was 0.2 g / m 2 , and obtain a highly efficient thermal transfer carbon ribbon back coating.
[0054] Example 5
[0055] (1) Under nitrogen atmosphere, 25 mmol of tetrakis(hydroxymethyl)phosphonium chloride and 160 mL of N,N-dimethylformamide were added to a reaction flask equipped with a tail gas absorption device, and after stirring, 42.5 mmol of vinyltrichlorosilane was added, and the mixture was reacted at 125° C. for 11 h. The mixture was cooled and crystallized, filtered, and the filter cake was washed with acetonitrile and dried to obtain an alkenyl cage siloxane monomer.
[0056] (2) Under nitrogen atmosphere, 22 mmol of 2,5-bis(trifluoromethyl)terephthalic acid, 47.3 mmol of alkenyl cage siloxane monomer and 285 mL of dichloromethane were added to the reaction flask. After stirring evenly, 9.9 mmol of 4-dimethylaminopyridine and 58.3 mmol of N,N-dicyclohexylcarbodiimide were added. The mixture was reacted at 35° C. for 24 h, and then distilled under reduced pressure and recrystallized from ethanol to obtain a diene fluorine-containing cage siloxane monomer.
[0057] (3) Under a nitrogen atmosphere, 10 mmol of pentaerythritol tetraacrylate and deionized water were added to a reaction flask. After uniform dispersion, 8 mmol of diene fluorinated caged siloxane monomer and 0.4 mmol of ammonium persulfate were added, and polymerization was carried out at 90° C. for 2 h. The temperature was lowered to 55° C., and the pH was adjusted to 8 with aqueous ammonia to obtain a cross-linked silicone acrylic copolymer.
[0058] (4) A 12% by weight cross-linked silicone acrylic copolymer was dissolved in 88% toluene. After being evenly diluted, it was directly coated on the back of the resin-based thermal transfer ribbon using a gravure coating machine. The coating amount was 0.25 g / m 2 , and obtain a highly efficient thermal transfer carbon ribbon back coating.
[0059] Comparative Example 1
[0060] (1) Under nitrogen atmosphere, 56 mmol of pentaerythritol (CAS No. 115-77-5, structural formula: ) and 450 mL of diethylene glycol dimethyl ether, stir evenly, add 92.4 mmol of vinyl trichlorosilane, react at 130 ° C for 10 hours, cool and crystallize, filter, wash the filter cake with acetonitrile, and dry to obtain an alkenyl cage-like silicone monomer.
[0061] (2) Under nitrogen atmosphere, 50 mmol of 2,5-bis(trifluoromethyl)terephthalic acid, 107 mmol of alkenyl caged organosilicon monomer and 625 mL of dichloromethane were added to a reaction flask. After stirring evenly, 20 mmol of 4-dimethylaminopyridine and 140 mmol of N,N-dicyclohexylcarbodiimide were added. The mixture was reacted at 25° C. for 16 h, and then distilled under reduced pressure and recrystallized from ethanol to obtain a diolefin fluorine-containing caged organosilicon monomer.
[0062] (3) Under a nitrogen atmosphere, 10 mmol of pentaerythritol tetraacrylate and deionized water were added to a reaction flask. After uniform dispersion, 5 mmol of diene fluorinated caged organosilicon monomer and 0.35 mmol of potassium persulfate were added, and polymerization was carried out at 80° C. for 2 h. The temperature was lowered to 50° C., and the pH was adjusted to 9 with aqueous ammonia to obtain an organosilicon acrylic copolymer.
[0063] (4) 8% by mass of organic silicone acrylic copolymer was dissolved in 92% toluene. After being evenly diluted, it was directly coated on the back of the resin-based thermal transfer ribbon using a gravure coating machine. The coating amount was 0.05 g / m 2 , and obtain the back-coated adhesive of the thermal transfer carbon ribbon.
[0064] Comparative Example 2
[0065] (1) Under a nitrogen atmosphere, 10 mmol of pentaerythritol tetraacrylate and deionized water were added to a reaction flask. After uniform dispersion, 5 mmol of alkenyl cage siloxane monomer (prepared in Example 1) and 0.35 mmol of potassium persulfate were added. The mixture was polymerized at 80° C. for 2 h, cooled to 50° C., and the pH was adjusted to 9 with aqueous ammonia to obtain an organosilicon acrylic copolymer.
[0066] (2) 8% by mass of organic silicone acrylic copolymer was dissolved in 92% toluene. After being evenly diluted, it was directly coated on the back of the resin-based thermal transfer carbon ribbon using a gravure coating machine. The coating amount was 0.05 g / m 2 , and obtain the back-coated adhesive of the thermal transfer carbon ribbon.
[0067] Comparative Example 3
[0068] (1) Under nitrogen atmosphere, 10 mmol of methyl methacrylate (CAS No. 80-62-6, structural formula: ) and deionized water, dispersed evenly, added 5mmol allyltrimethoxysilane (CAS No. 2551-83-9, structural formula ) and 0.35 mmol potassium persulfate, polymerized at 80°C for 2 h, cooled to 50°C, and adjusted the pH to 9 with aqueous ammonia to obtain an organosilicon acrylic copolymer.
[0069] (2) 8% by mass of organic silicone acrylic copolymer was dissolved in 92% toluene. After being evenly diluted, it was directly coated on the back of the resin-based thermal transfer carbon ribbon using a gravure coating machine. The coating amount was 0.05 g / m 2 , and obtain the back-coated adhesive of the thermal transfer carbon ribbon.
[0070] Antistatic performance test: The antistatic performance test was carried out using a ZC-90G high insulation resistance meter. The thermal transfer carbon ribbons coated with back glue prepared in the embodiments and comparative examples were cut into samples to be tested and placed on the work table of the high insulation resistance meter. Electrodes with an outer diameter of 8 cm and an inner diameter of 7 cm were placed on the sample surface to measure the sample resistance. The surface resistance was measured again after working for 60 days under normal conditions.
[0071] Table 1 Antistatic performance test
[0072]
[0073]
[0074] From the test results in the above table, it can be seen that with the increase of the content of the cross-linked silicone acrylic copolymer and the coating amount of the carbon ribbon, the antistatic performance of the thermal transfer carbon ribbon is significantly improved. The surface resistance value of Example 4 after being placed for one day is 6.51×10 7 Ω, after 60 days of storage, the resistance value did not change much, only 9.42×10 7Ω, indicating that the static charge generated during the printing process is effectively released; this is because the cross-linked silicone acrylic copolymer contains quaternary phosphonium salts, and the phosphorus atom ion radius in the quaternary phosphonium salts is large, which enhances its polarization effect and makes it easier to interact with negatively charged charges or substances through electrostatic action, forming a stable protective layer on the surface of the substrate, thereby quickly extracting the static charge generated during the printing friction process from the material surface, so that the generated static charge does not accumulate, and at the same time, the quaternary phosphonium salt is chemically grafted with acrylic monomers to initiate polymerization, and is bonded to the main body of the material in the form of a cross-linked network structure, so the antistatic performance will not migrate and lose with time, and has a persistent antistatic effect. Comparative Examples 1, 2, and 3 do not contain quaternary phosphonium salts, have high resistance, are prone to static electricity during use, and do not have an antistatic effect.
[0075] Limiting oxygen index test: Use oxygen index meter to test.
[0076] Vertical burning grade test: tested using UL-94 vertical burning test machine.
[0077] Table 2 Flame retardant performance test
[0078]
[0079]
[0080] It can be seen from the test results in the above table that with the increase of the content of the cross-linked silicone acrylic copolymer and the coating amount of the carbon ribbon, the flame retardant performance of the thermal transfer carbon ribbon is significantly improved, and the flame retardant material level is reached in the embodiments. This is because, on the one hand, the phosphorus and silicon in the cross-linked silicone acrylic copolymer can produce synergistic flame retardancy, phosphorus will catalyze the formation of carbon, and the caged silicon increases the thermal stability of these carbon layers. The acidic gas released by the phosphorus element combines with the silicon element to form silicates, which promotes the formation of phosphoric acid compounds. The layered silica formed by the degradation of siloxane can prevent the oxidation of the carbon layer and form a more complete protective film, which can more effectively isolate heat and oxygen and delay the combustion process; on the other hand, the cross-linked silicone acrylic copolymer is obtained by initiating polymerization of the two double bonds of the double-terminal alkenyl caged silicone monomer and the four double bonds of pentaerythritol tetraacrylate, forming a hyperbranched cross-linked network structure. When the material burns, a dense protective layer can be formed to isolate oxygen from the internal material, thereby slowing down or preventing the combustion process.
[0081] Comparative Example 1 does not contain phosphorus element, but contains a dense cross-linked network structure with a limiting oxygen index of 22.3%; Comparative Example 2 does not contain phosphorus element, cannot produce phosphorus-silicon synergistic flame retardant effect, and the formed cross-linked structure is not as dense as that of the embodiment; Comparative Example 3 does not contain phosphorus element, and a straight chain structure is formed, which cannot play a physical barrier role and has the worst flame retardant performance.
[0082] Wear resistance test: Use a friction coefficient meter to measure the dynamic friction coefficient of the back-coated adhesive to evaluate the smoothness of the back-coated adhesive.
[0083] Heat resistance test: Use Zebra ZM400 barcode printer to test the heat resistance of the back-coated adhesive. Adjust the heat resistance gear until the carbon ribbon breaks through. At this time, the heat resistance gear is the maximum heat resistance gear of the back-coated adhesive.
[0084] Printing performance test: During the printing process, the noise decibel is tested using a noise analyzer to determine the smoothness of the printing process.
[0085] Adhesion performance test: After printing 20,000 sheets of ribbon continuously with a Zebra ZM400 barcode printer, observe whether there is back-coated adhesive material on the print head to evaluate the adhesion of the back-coated adhesive.
[0086] Table 3 Back coating performance and printing performance test.
[0087] Dynamic friction coefficient Heat resistance gear noise Adhesion Example 1 0.05 22 80 No glue falling off Example 2 0.04 24 78 No glue falling off Example 3 0.03 26 77 No glue falling off Example 4 0.02 28 75 No glue falling off Example 5 0.02 28 74 No glue falling off Comparative Example 1 0.06 20 81 Slight glue peeling Comparative Example 2 0.11 18 89 Serious glue peeling Comparative Example 3 0.12 16 92 Serious glue peeling
[0088] From the test results in the above table, it can be seen that a fluorocarbon protective film is formed on the surface of the fluorine-containing carbon ribbon in the back-coating adhesive, which can not only reduce the friction coefficient of the surface and improve the wear resistance, but also prevent the occurrence of problems such as corrosion and adhesion; the fluorine element has extremely high chemical stability, its atomic radius is small, and its electronegativity is strong, so that the chemical bonds in the fluoride molecules are very strong, and they will not fail due to thermal decomposition or chemical reaction in a high temperature environment, thereby maintaining their lubrication properties. The carbon ribbon back-coating adhesive prepared by the present invention has good heat resistance and wear resistance, and prints smoothly and has good bonding performance. It strengthens the heat conduction and lubrication effect during the printing process, and can effectively alleviate the problem of print head wear.
[0089] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a high-efficiency thermal transfer carbon ribbon back coating adhesive, characterized in that: The preparation method is carried out according to the following steps: Step (1), under nitrogen atmosphere, add pentaerythritol tetraacrylate and deionized water to a reaction flask, disperse them uniformly, and then add The diene fluorine-containing caged siloxane monomer and the initiator are polymerized at 75-90° C. for 1-3 hours, the temperature is lowered to 45-55° C., and the pH is adjusted to 8-9 with aqueous ammonia to obtain a cross-linked silicone acrylic copolymer; Step (2), dissolving 8-12% by weight of the cross-linked silicone acrylic copolymer in 88-92% toluene, and after it is evenly diluted, directly coating it on the back of the resin-based thermal transfer ribbon on a coating machine using a gravure coating method, with a coating amount of 0.05-0.25 g / m 2 , and obtain a highly efficient thermal transfer carbon ribbon back coating.
2. The method for preparing a high-efficiency thermal transfer carbon ribbon back coating adhesive according to claim 1, characterized in that: In the step (1), the initiator is any one of potassium persulfate, ammonium persulfate or benzoyl peroxide.
3. The method for preparing a high-efficiency thermal transfer carbon ribbon back coating adhesive according to claim 1, characterized in that: In the step (1), the molar ratio of pentaerythritol tetraacrylate, diene fluorine-containing caged siloxane monomer and initiator is 1:0.5-0.8:0.02-0.
05.
4. The method for preparing a high-efficiency thermal transfer carbon ribbon back coating adhesive according to claim 1, characterized in that: The method for preparing the diene fluorine-containing caged siloxane monomer in step (1) is carried out according to the following steps: Step S1, under a nitrogen atmosphere, adding tetrakis(hydroxymethyl)phosphonium chloride and a solvent to a reaction flask equipped with a tail gas absorption device, stirring evenly, adding vinyltrichlorosilane, stirring for reaction, cooling and crystallizing after the reaction is completed, filtering, washing the filter cake with acetonitrile, and drying to obtain an alkenyl cage siloxane monomer; Step S2, under a nitrogen atmosphere, add 2,5-bis(trifluoromethyl)terephthalic acid, alkenyl cage siloxane monomer and dichloromethane into a reaction flask, stir evenly, add 4-dimethylaminopyridine and N,N-dicyclohexylcarbocyanine, stir to react, after the reaction is completed, distill under reduced pressure, and recrystallize from ethanol to obtain a diene fluorine-containing cage siloxane monomer.
5. The method for preparing a high-efficiency thermal transfer carbon ribbon back coating adhesive according to claim 4, characterized in that: The solvent in step S1 is any one of diethylene glycol dimethyl ether, N,N-dimethylformamide or xylene.
6. The method for preparing a high-efficiency thermal transfer carbon ribbon back coating adhesive according to claim 4, characterized in that: In the step S1, the molar ratio of tetrakis(hydroxymethyl)phosphonium chloride to vinyltrichlorosilane is 1:1.5-1.
8.
7. The method for preparing a high-efficiency thermal transfer carbon ribbon back coating adhesive according to claim 4, characterized in that: In step S1, the reaction temperature is 120-140° C. and the reaction time is 5-12 h.
8. The method for preparing a high-efficiency thermal transfer carbon ribbon back coating adhesive according to claim 4, characterized in that: In the step S2, the molar ratio of 2,5-bis(trifluoromethyl)terephthalic acid, alkenyl cage siloxane monomer, 4-dimethylaminopyridine and N,N-dicyclohexylcarboximide is 1:2.05-2.2:0.3-0.5:2.5-3.
2.
9. The method for preparing a high-efficiency thermal transfer carbon ribbon back coating adhesive according to claim 4, characterized in that: In step S2, the reaction temperature is 20-35° C. and the reaction time is 12-24 h.
10. A high-efficiency thermal transfer carbon ribbon back coating, characterized in that: Obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of acrylate-modified silicone polymer and application in thermal transfer ribbon
CN114656601B
Vinyl silicon-containing cage-shaped phosphate flame retardant and preparation method thereof
CN104479077A
Resin for bar code thermal transfer ribbon back coating and preparation method thereof as well as bar code thermal transfer ribbon back coating liquid and application thereof
CN107903364A